Implied transaction costs by leland option pricing models: A new approach and empirical evidence - Abdullah, Mimi Hafizah; Li, Steven (2011)
Estimation of transaction costs in stock market is an important issue for stock trading, asset pricing, andstock market regulation etc. and it is often done by combining the bid-ask spread estimate with commissions and other fees provided by market participants which can be subjective. This study aims to offer an innovative way as an alternative to estimate the total transaction costs in stock trading via the implied transaction costs by using the Leland option pricing models. The effectiveness of this new approachis tested by using the S&P/ASX 200 index call options data.Based on the actual transaction costs on the Australian Securities Exchange (ASX) documented by previous studies and the Roll’s model,the empirical results reveal that this new approach can provide a reliable transaction costs estimate on stock trading in the ASX.Furthermore, the accuracy of the implied transaction costs and across option moneyness and maturity is investigated.